Unusual presentation of Abdominal TB: A Case Report - Pervin, Shelina (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Abdominal TB is an increasingly common disease that poses diagnostic challenges, as the nonspecific features of the disease which may lead to diagnostic delays and development of complications. Tuberculosis can involve any part of the gastrointestinal tract and is the sixth most frequent site of extrapulmonary involvement. A 30 years old lady mother of two children was present with a right large complex adnexal mass with huge ascites diagnosed as a case of abdominal tuberculosis is reported. She had a past history of abdominal TB on 2010 and treated by antitubercular drugs for 6 months( 4 drugs for 2months and 2 drugs for 4 months regimen). This time she was managed jointly by Gynaecological, Surgery and Medicine department. As she was present with a right large complex adnexal mass with huge ascites which distressed her. So judicious decision was taken for her including both surgical and medical management. Bangladesh J Obstet Gynaecol, 2021; Vol. 36(2): 132-134